Modern Meteoric 36Cl Deposition in the Atacama Desert, Chile. Issue 21 (2nd November 2020) - Wang, Fan; Michalski, Greg
Abstract: Modern atmospheric deposition along a west‐east transect in the Atacama Desert, Chile, was collected to constrain the meteoric 36 Cl/Cl ratio and 36 Cl deposition flux. The 36 Cl deposition flux had a threefold change, from 3.62(±0.18) to 11.6(±0.2) atoms m −2  s −1, going from the coast to the high Andes. The 36 Cl deposition was mainly as dry deposition, and the magnitude and differences between sites were attributed to stratosphere‐troposphere transport and chloride deficits by acid displacement, respectively. The meteoric 36 Cl/Cl ratios varied greatly from 31.5(±1.1) × 10 −15 to 247(±10) × 10 −15, which was attributed to local inputs of oceanic chloride near the coast or chloride minerals entrained from nearby salt playas. This study presented refined estimates of the 36 Cl deposition flux and meteoric 36 Cl/Cl ratio in a desert region in southern tropical zone. The data set will provide a baseline for using natural 36 Cl abundances to date salt accumulation in the Atacama. Plain Language Summary: 36 Cl is a radioactive chlorine isotope found in the atmosphere and can be used in many ways, from determining ages of soils and groundwaters to tracing origins of salts and groundwater flow paths. In order to use meteoric 36 Cl, we must know how much is deposited from the atmosphere to the surface. There are only a few studies of 36 Cl deposition in southern hemisphere, even less in extraordinarily dry environments, which hinders its use in desert regions south of the equator. We have measured the 36 Cl deposition along a west‐east transect in the Atacama Desert in northern Chile and developed a simple explanation for our results. Future work will use this deposition rate to determine the duration of soil salt accumulation in the Atacama and understand changes in climate (precipitation) in the past. Key Points: 36 Cl deposition has been measured across a west‐east transect in the Atacama Desert, Chile Elevated 36 Cl dry deposition in the region was attributed to enhanced stratosphere‐troposphere transport over the Andes Variations in the 36 Cl deposition flux along the transect were attributed to chloride displacements by atmospheric acids